Ephrin regulation of palate development - Benson, M. D.; Serrano, Maria J. (Frontiers in Physiology, 2012)
Studies of palate development are motivated by the all too common incidence of cleft palate, a birth defect that imposes a tremendous health burden and can leave lasting disfigurement. Although mechanistic studies of palate growth and fusion have focused on growth factors such at Transforming Growth Factor ß-3 (Tgfß3), recent studies have revealed that the ephrin family of membrane bound ligands and their receptors, the Ephs, play central roles in palatal morphogenesis, growth, and fusion. In this mini-review, we will discuss the recent findings by our group and others on the functions of ephrins in palatal development.